The influence of serial feeding of drinks at different temperatures on thermoregulatory responses during cycling - Lee, J. K. W.; Maughan, R. J.; Shirreffs, S. M. (Journal of Sports Sciences, 2008)
In this study, we examined thermoregulatory responses to ingestion of separate aliquots of drinks at different temperatures during low-intensity exercise in conditions of moderate heat stress. Eight men cycled at 50% (s = 3) of their peak oxygen uptake (VO2peak) for 90 min (dry bulb temperature: 25.3°C, s = 0.5; relative humidity: 60%, s = 5). Four 400-ml aliquots of flavoured water at 10°C (cold), 37°C (warm) or 50°C (hot) were ingested after 30, 45, 60, and 75 min of exercise. Immediately after the 90 min of exercise, participants cycled at 95%VO2peak to exhaustion to assess exercise capacity. There were no differences between trials in rectal temperature at the end of the 90 min of exercise (cold: 38.11°C, s = 0.30; warm: 38.10°C, s = 0.33; hot: 38.21°C, s = 0.30; P = 0.765). Mean skin temperature between 30 and 90 min tended to be influenced by drink temperature (cold: 34.49°C, s = 0.64; warm: 34.53°C, s = 0.69; hot: 34.71°C, s = 0.48; P = 0.091). Mean heart rate from 30 to 90 min was higher in the hot trial (129 beats · min-1, s = 7; P < 0.05) than on the cold (124 beats · min-1, s = 9) and warm trials (126 beats · min-1, s = 8). Ratings of thermal sensation were higher on the hot trial than on the cold trial at 35 and 50 min (P < 0.05). Exercise capacity was similar between trials (P = 0.963). The heat load and debt induced by periodic drinking resulted in similar body temperatures during low-intensity exercise in conditions of moderate heat stress due to appropriate thermoregulatory reflexes.